Applicability evaluation of tree volume equation for Abies kawakamii (Hayata) Ito based on stem analysis data in Taiwan. Issue 5 (3rd September 2021) - Li, Pei-Hua; Liao, Min-Chun; Tzeng, Hsy-Yu; Tseng, Yen-Hsueh; Yen, Tian-Ming
ABSTRACT: Abies kawakamii (Taiwan fir) typically constitutes pure forest distributed at 3, 100–3, 600 m above sea level in Taiwan. Its volume was first investigated in 1963 using aerial photography to identify the growing stock of the forest. In 1973, Taiwan Forestry Bureau established a fir volume estimation equation by considering Taiwan spruce and Taiwan fir stands. However, due to cutting natural forest is not permitted in Taiwan, it was difficult to reconstruct specific volume equation for Taiwan fir. We can only use and collect the uprooted trees as samples for this study by Typhoon Soudelor in 2015. We used these samples for estimation and used the remaining trees for verification and tested the suitability of six equations (models) for Taiwan fir volume estimation. We found that the Schumacher equation was suitable for juvenile trees, and the generalized combined-variable equation was suitable for semi-mature trees. The Schumacher equation (a logarithmic equation) and generalized combined-variable equation demonstrated the better suitability for volume estimation. However, when a juvenile was considered in the estimation, the generalized combined-variable equation provided underestimations. Thus, the Schumacher equation (V = aD b H c ) was the better model for our test. The new tree volume estimation equation for Taiwan fir in the Mt. Xue region is presented as follows: V = 0.00003663 × D 1.6693 × H 1.4003 .